2002
DOI: 10.1063/1.1524032
|View full text |Cite
|
Sign up to set email alerts
|

Formation of epitaxial Au/Ni/Au ohmic contacts to p-GaN

Abstract: We have designed a promising contact scheme to p-GaN, where Au/Ni/Au layers are deposited on p-GaN and annealed in air for 30 min at 470 °C to produce low-resistivity ohmic contacts. The Au layer in contact with p-GaN grows epitaxially via domain matching epitaxy, which acts as a template for NiO growth via lattice matching epitaxy. The 〈111〉 oriented gold rotates 30° in the basal (0001) plane of GaN by 30° with the following orientation relationship: [111]Au//[0001]GaN; [112̄]Au//[21̄1̄0]GaN. As a result, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Ho et al suggest that the formation of p-NiO by oxidizing the Ni layer leads to a reduction of the Schottky barrier height (SBH) of the Ni/Au contact to p-GaN, and the granular Au particles in the NiO matrix form a high conductive cermet-like matter [1]. On the other hand, the schemes of NiO/p-GaN [9] and Au/NiO/p-GaN [3,4] did not show a low-resistance Ohmic contact. It was reported that the prefabricated NiO layer prevented interdiffusion and metallurgic reaction of Ni, Au, N, Ga [10][11], and alleviated the reversion reaction from Au/Ni/GaN to NiO/Au/GaN [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al suggest that the formation of p-NiO by oxidizing the Ni layer leads to a reduction of the Schottky barrier height (SBH) of the Ni/Au contact to p-GaN, and the granular Au particles in the NiO matrix form a high conductive cermet-like matter [1]. On the other hand, the schemes of NiO/p-GaN [9] and Au/NiO/p-GaN [3,4] did not show a low-resistance Ohmic contact. It was reported that the prefabricated NiO layer prevented interdiffusion and metallurgic reaction of Ni, Au, N, Ga [10][11], and alleviated the reversion reaction from Au/Ni/GaN to NiO/Au/GaN [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, from among all contact structures on p-GaN the Au/Ni/p-GaN [8][9][10][11][12][13][14][15][16][17] structure seems to be the most suitable thanks to relatively good values of the specific contact resistance and in the case of very thin layers also thanks to optical transparency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the best contact structure to p-GaN seems to be the Au/Ni structure, namely because of the relatively good values of contact resistivities 10 −4 to 10 −6 Ωcm 2 and its optical transparency. It was found that oxidation of such a thin Ni/Au bilayer in air or in water vapour brings about a change of Ni into NiO, diffusion of Au into the interface and at the same time an improvement in the transparency of the metallization layer [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%